WATER DEFICIT IN THE MAIN EDIFICATES OF THE KARAKALPAKSTAN DESERT - G. Sabirov; D. Sabirov (Galaxy International Interdisciplinary Research Journal, 2024)
In the harsh xerothermic conditions of the desert, only a few species can grow without irrigation, so for phytomelioration it is necessary to select drought-resistant forage plants with high adaptive properties to these living conditions. These works should be based on knowledge of the biological and physiological characteristics of Karakalpak pasture plants, including their water regime, since the main limiting factor in plant life under these conditions is a pronounced lack of water in the soil and air. For this purpose, we have studied the water regime of the main pasture plants, such as black saxaul - Haloxylon aphyllum (Minkw), under natural growing conditions for many years (1973-2013). Iljin, oriental saltwort or keireuk – Salsola orientalis S.G.Gmel., saltmarsh or biyurgun – Anabasis salsa (C.A.Mey.) Benth., tree-like solyanka or black wight – Salsola arbusculiformis Drob., white earth wormwood – Artemisia terrae albae H.Krasch and curly spiny – Artaphaxis spinosa L.